Titrating Growth Hormone Dose to High-Normal IGF-1 Levels Has Beneficial Effects on Body Fat Distribution and Microcirculatory Function Despite Causing Insulin Resistance - van Bunderen, Christa C.; Meijer, Rick I.; Lips, Paul; Kramer, Mark H.; Serné, Erik H.; Drent, Madeleine L. (Frontiers in Endocrinology, 2021)
To clarify the mechanism underlying the described U-shaped relation of both low and high levels of IGF-1 with cardiovascular disease this study explores the effect of decreasing and increasing growth hormone dose in GH deficient adults on (micro)vascular function, body composition and insulin resistance. In this randomized clinical trial, thirty-two subjects receiving GH therapy with an IGF-1 concentration between −1 and 1 SD score (SDS) for at least one year were randomized to receive either a decrease (IGF-1 target level of −2 to −1 SDS) or an increase of their daily GH dose (IGF-1 target level of 1 to 2 SDS) for a period of 24 weeks. Microvascular endothelium (in)dependent vasodilatation and vasomotion, vascular stiffness by pulse wave analysis, and HOMA-IR were measured. At the end of the study 30 subjects (65.6% men, mean age 46.6 (SD 9.9) years) were analyzed. There was a favorable effect of increasing the IGF-1 level on waist circumference compared to decreasing the IGF-1 level (p=0.05), but a detrimental effect on insulin resistance (p=0.03). Decreasing IGF-1 level significantly lowered the endothelial domain of vasomotion (p=0.03), whereas increasing IGF-1 level increased the contribution of the neurogenic domain (p=0.05). This change was related to the favorable change in waist circumference. In conclusion, increasing IGF-1 levels was beneficial for body composition but detrimental with respect to insulin resistance. The contribution of the neurogenic vasomotion domain increased in parallel, and could be explained by the favorable change in waist circumference. Clinical Trial Registration ClinicalTrials.gov, identifier NCT01877512.